Characteristics of the tragic hero in the plays of Salah Abdel Sabour (Journal of the College of Basic Education, 2022)
Man realized from time immemorial until now through collective communication, searching for indicationsMeanings and values ​​that paint a picture of the hero or heroism, as a characteristic that does notAll the heroic nature, which are just the features that define the heroic symbol. His identity is defined by his being a symbolThe group, on the other hand, considers it the face of the collision with the problems of its time. Because he has several attributes that qualify himbecause this post is taken. Among these features and characteristics that frame the concept of heroic meditation is The principle of challenging and conveying the impossible by force of will, and sometimes extraordinary performance.